Pelatihan Pembuatan Obat Kumur Dari Sari Daun Sereh Dan Kecombrang Di Desa Biru-Biru Kecamatan Deli Tua Kab Deli Serdang - Muhammad Gunawan; Siti Aisyah Tanjung; Melati Yulia Kusumastuti; Enny Fitriani (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Gingivitis is an oral health disease characterized by inflammation of the gingival tissue, which appears reddish. One of the ways to prevent and treat gingivitis is by using mouthwash. Herbal mouthwash made from lemongrass and torch ginger leaves is used to treat gingivitis. Lemongrass and torch ginger leaves are known to have antimicrobial activity against the bacteria that cause gingivitis. Public knowledge about the mouthwash made from lemongrass and torch ginger extract increased by 41%. This indicates an improvement in public understanding of the benefits of lemongrass and torch ginger extract mouthwash for preventing gingivitis and the economic value of the herbal mouthwash product. A gargle preparation is a formulation containing active substances that can prevent or kill bacteria that cause dental caries. Plants commonly used by the community to address this problem include lemongrass and torch ginger. Traditionally, lemongrass and torch ginger leaves have been used to treat dental diseases. The purpose of this community service activity was to provide training on the production of mouthwash made from lemongrass and torch ginger extract in Biru-biru Village, Deli Tua District, Deli Serdang Regency, North Sumatra Province. This community service program was divided into two activities: the first was education on oral and dental health, and the second was training on the preparation of lemongrass and torch ginger extract mouthwash. The results of this activity showed an increase in public knowledge about oral and dental health and the ability to produce herbal mouthwash made from lemongrass and torch ginger extract.